Faktor-faktor yang mempengaruhi remaja awal mengendarai sepeda motor - Elsinta Aknesia Prabulingga (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study to know the Factors Affecting Early Teenager Riding Motorcycle. This research was conducted in X village Blora Regency. This data collection technique uses a triangulation approach, namely sampling, observation and interviews. There are two aspects that are assessed include, internal factors and external factors. Of these factors that most influence early adolescents riding a motorcycle are internal factors. The percentage of internal factors is 66.66%. This internal factor consists of parental control indicators, student motivation, and violation of rules in traffic. Of these indicators the most influential are parental control indicators. While external factors less influence early teens riding a motorcycle. The percentage of external factors is 46.66%)Keyword: early teenagers, internal factors, external factors,riding a motorcycle